METHODOLOGICAL PROBLEMS IN THE EVALUATION OF OCCUPATIONAL EXPOSURE OF HEALTH WORKERS - Хамитов, Тулеген Нургалиевич (Medicine in Kuzbass, 2018)
Maintaining the health of the working population is the key to successful economic and social development of any state. Currently we are looking for when planning strategies for health promotion the shift in focus from a clinical approach towards prevention programmes. In this regard, assessment of professional risk is one of the most effective methods of analysis of the influence of production factors on the workers’ health. Finding effective methods for early diagnosis professionally conditioned and socially significant diseases allows formation of high-risk groups. The results of complex analysis can become a basis for the systematic management of occupational risks. For the analysis and occupational risk assessment requires the creation of databases for characterizing the impact of harmful factors in the period of employment.